2021
DOI: 10.1002/fes3.298
|View full text |Cite
|
Sign up to set email alerts
|

The combination of different nitrogen fertilizer types could promote rice growth by alleviating the inhibition of straw decomposition

Abstract: Straw return plays an important role in the improvement of farmland ecological environments, increasing soil fertility, crop quality, and yield. However, in the early growth of rice (Oryza sativa L.), straw decomposition and rice growth may be inhibited by suboptimal carbon/nitrogen (C/N) ratios. We, therefore, explored methods that could alleviate the inhibition of straw decomposition using different combinations of ammonium bicarbonate and compound fertilizer. No fertilizer (CK) and compound fertilizer (S0) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…It was suggested that compared with the application of compound fertilizer alone, application of Ammonium N fertilizers can supply available N faster for the purpose of straw decomposition [ 21 ]. In this study, we showed that ammonium bicarbonate-substituted compound fertilizer (A2 treatment) significantly improved straw decomposition rate, consistent with previous observations [ 22 , 23 ]. However, we also observed no increase in the straw decomposition rates of A3 and IA4 compared with A0, indicating that an excessive increase in the proportion of ammonium bicarbonate alone in basal fertilizer did not provide a long-term N source for straw decomposition.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was suggested that compared with the application of compound fertilizer alone, application of Ammonium N fertilizers can supply available N faster for the purpose of straw decomposition [ 21 ]. In this study, we showed that ammonium bicarbonate-substituted compound fertilizer (A2 treatment) significantly improved straw decomposition rate, consistent with previous observations [ 22 , 23 ]. However, we also observed no increase in the straw decomposition rates of A3 and IA4 compared with A0, indicating that an excessive increase in the proportion of ammonium bicarbonate alone in basal fertilizer did not provide a long-term N source for straw decomposition.…”
Section: Discussionsupporting
confidence: 92%
“…At maturity, the representative plants were randomly collected to determine the N content of the rice using the ECS 4024 CHNS-O Classic Analyzer (Costech, Italy). Apparent nitrogen use efficiency (ANUE, %), agronomic nitrogen use efficiency (AE, kg/kg), physiological nitrogen use efficiency (PNUE, kg/kg), and partial factor productivity of nitrogen (PFP N , kg/kg) were calculated according to the following equations [ 23 ]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that, when the soil has reached high fertility through fertilization, the improvement of fertilization in soil nutrients was lower than that at low fertility (Fippin, 1937;Chen et al, 2021) and (2) poor microbial activity under excess fertilization. The process of straw decomposition by soil microorganisms to release nutrients is influenced by several factors, such as temperature, humidity, soil physical and chemical properties, fertilization, and pesticides (Li et al, 2017;Tang et al, 2021). Excess fertilization can cause soil compaction and acidification, which influence soil microbial community composition and ecological function (Zhao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Field trial‐based European studies have also found that integrating fertilisation with organic amendment applications led to consistently higher agronomic performance than crops treated with only one or the other (Macholdt et al, 2019; Sihvonen et al, 2021). This approach has also been applied to farming systems in the developing world (Abid et al, 2020; Qazi & Khan, 2020), particularly in the cultivation of rice in which substantial improvements to crop performance and quality have been obtained through combining synthetic N additions with K inputs (Ye et al, 2021), retention and reincorporation of residues (Tang et al, 2021). An important next step is to connect findings from the efficiency index to soil quality.…”
Section: Discussionmentioning
confidence: 99%